strategi Strategi diferensiasi produk sebagai upaya meningkatkan daya saing bank syariah di Indonesia - aulia, keysya valentina (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze product differentiation strategies as an effort to improve the competitiveness of Islamic banks in Indonesia. The method used is a descriptive qualitative approach using secondary data from scientific journals, previous research results, and official Islamic banking publications. The results of the study show that differentiation strategies are carried out through four main dimensions, namely product innovation based on segment needs, improvement of product and service quality, utilization of digital technology and fintech, and a customer-oriented marketing approach. Innovations such as pre-retirement financing, service digitalization, and the use of AI have been proven to increase loyalty and strengthen the image of Islamic banks. However, challenges such as low financial literacy, limited human resources, and Sharia supervision of digital innovation still need to be addressed. Overall, product differentiation based on Sharia values can create competitive advantages and sustainability for Islamic banks in Indonesia.